Deconstructing Gender Stereotypes in Leak (Komunitas, 2015)
The belief of Balinese people towards leak still survive. Leak is a magic based on durgaism that can transform a person from human to another form, such as apes, pigs, etc. People tend to regard leak as evil. In general, the evilness is constructed in gender stereotypes, so it is identified that leak are always women. This idea is a power game based on the ideology of patriarchy that provides legitimacy for men to dominate women with a plea for social harmony. As a result, women are marginalized in the Balinese society. Women should be aware of so it would provide encouragement for them to make emancipatory changes dialogically. Kepercayaan orang Bali terhadap leak tetap bertahan sampai saat ini. Leak adalah sihir yang berbasiskan durgaisme yang dapat mengakibatkan seseorang bisa merubah bentuk dari manusia ke wujud yang lain, misalnya kera, babi, dll. Leak termasuk magi hitam sehingga dinilai bersifat jelek. Pada umumnya perempuan diidentikkan dengan leak sehingga melahirkan asumsi yang bermuatan steriotip gender bahwa leak = perempuan. Gagasan ini merupakan permainan kekuasaan berbasis ideologi patriarkhi dan sekaligus memberikan legitimasi bagi laki-laki untuk menguasai perempuan dengan dalih demi keharmonisan sosial. Akibatnya, perempuan menjadi termarginalisasi pada masyarakat Bali.  Perempuan harus menyadarinya sehingga memberikan dorongan bagi mereka untuk melakukan perubahan secara dialogis emansipatoris.